Sustainability of micro and small enterprises during COVID-19 pandemic / Baderisang Mohamed and Mohd. Sukor Md. Yusoff - Mohamed, Baderisang; Md. Yusoff, Mohd. Sukor (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2021)
COVID-19 has had a significant impact not only on the well-being and health of people but also on the economy. Micro and Small Enterprises (MSEs) are an essential part of the economy in Malaysia (Bai, Quayson, & Sarkis, 2021). Global epidemics such as COVID-19 expose MSEs to different types of challenges that risk their existence in the market. From the time COVID-19 emerged, it has negatively affected both economies of many nations and human health. Various restrictions and conditions have been imposed in different countries to limit the spread of the virus. Such limitations comprise social distancing, quarantine, and travel restrictions (Bai et al., 2021). These conditions have resulted in a slowed system of demand and supply of goods and services in different nations. The effects of COVID-19 have been experienced across all sectors of the economy, including MSEs (Bai et al., 2021) This paper briefly explores various challenges that MSEs have faced during the COVID-19 pandemic and various strategies that have enabled these businesses to sustain themselves over this period.